Long-term meteorological trends of atmospheric precipitation in the Nura river basin (the Сentral Кazakhstan) - Zhangozhina, G.M.; Czernykh, D.V. (Fundamental and Experimental Biology, 2020)
For living organisms, the main indicators are the average values are meteorological and hydrological parameters that determine the coverage of the survival of species. Currently, all research on the trend in the land-scape of river basins should begin with an analysis of climate change, which is currently undergoing rapid dynamic changes. The purpose of the study is to analyze the long meteorological trends of atmospheric humidity of the Nura River Valley. In the presented study, we analyzed the daily data of two weather stations of the Central Kazakhstan for the period from 1939 to 2019 within. The territory of the Nura river basin belongs to areas of pronounced insufficient moisture. A distinctive feature of the river is that the bulk of the annual flow takes place in a short period of spring flood (early April to mid-May, 4–5 months). Within the Nura river basin, reliable trends of significant changes in annual, semi-annual and seasonal amounts of atmospheric precipitation have been revealed. All identified trends have positive indicators. The results can be used for agricultural planning in the context of climate change in the Central Kazakhstan.